All-fiber mode converter based on superimposed long period fiber gratings - 薛艳茹;毕卫红;金娃;田朋飞;江鹏;刘强;靳云 (Optoelectronics letters, 2018)
In this paper, a novel broadband all-fiber mode converter is proposed and experimentally demonstrated. Through writing a pair of superimposed long period fiber gratings（SLPFGs） in tow-mode fiber（TMF） with a CO_2 laser, the mode converter can realize the conversion from LP_（01） to LP_（11） owing to the phase matching condition. Numerical and experimental results show that the bandwidth of this mode converter is 3 times broader than that of a single grating converter. The converter has low loss, high coupling efficiency, small size and is easy to fabricate, so it can be widely used in mode-division multiplexing.